That was then, this is now : contemporary archaeology and material cultures in Australia - Clarke, Anne, 1959-; Frederick, Ursula, 1970- (Cambridge Scholars Publishing, 2016)
That Was Then, This Is Now is a compendium of innovative research into the ideas, experiences, and iconographies embodied in materialities of the recent past. Drawing upon a variety of disciplines, including archaeology, history, art, and cultural geography, authors examine themes of relevance to the contemporary world, such as the impacts of automobility, the invisible effects of radioactivity, and the scale of future cities. It serves as a reminder, moreover, that issues that confront us as global citizens - mass consumption, population growth, technological development, and the conditions o.